Local School Desegregation Practices in Sweden - Ali Osman; Stefan Lund (Education Sciences, 2022)
The focus of this paper is to examine the desegregation of hyper-segregated schools in Sweden. In this paper, our focus is on the practice(s) of desegregation in four Swedish municipalities. This study is based on interviews with municipal school politicians, school headmasters, and municipal school officials. Theoretically, the study departs from the theory of steering. This study shows that the municipalities use a strong belief in the peer effect to legitimise their decisions to desegregate hyper-segregated schools. Their decisions ignore a substantial research body that could lead to the development of different types of pedagogies that are relevant for these types of schools.